The Roman porticus: colonnades in Rome’s built environment, c. 200 BCE - 100 CE - White, B. J. (2023)
In recent years, space has proved a major theoretical and methodological vehicle for exploring social, cultural and political history. While space is produced by architectural structures, it also a product of the citizens that interact with them. It is precisely in this dialectic that this study employs the term ‘built environment’. In this thesis, I examine the developing forms and functions of a particular space, the porticus, and contextualise it in Rome’s built environment from 200 BCE to 100 CE. A primary function of Roman porticus was their framing of social interaction. By the second century CE, they provided the city of Rome with a cohesive columnar scenography, blending the routines of daily life to the intercolumnar rhythms of its architectural environment. This thesis investigates how and why.